Emerging Trends and Challenges of IoT in Smart Healthcare Systems, Smart Cities and Education - Khan, Faheem (Sensors (Basel, Switzerland), 2024)
Due to the rapid growth of science and technology, many modern devices are being developed to support healthcare and education systems [...].Due to the rapid growth of science and technology, many modern devices are being developed to support healthcare and education systems [...].